Educational mismatch, gender, and satisfaction in self-employment: The case of Russian-language internet freelancers. (June 2015) - Shevchuk, Andrey; Strebkov, Denis; Davis, Shannon N.
Highlights: Using data from Russian-language internet freelancers, we examine horizontal educational mismatch and socio-economic outcomes. The effects of educational mismatch on earnings, job satisfaction, and perceived job mobility are estimated. The combined effects of working outside one's field of study and caregiving for small children on socio-economic outcomes are estimated. We find that educational mismatch has differential influence on women's and men's experience. Women who work outside their field of study while caring for their small children are in the most vulnerable position. Abstract: In this paper, we examine the effect of horizontal educational mismatch on socio-economic outcomes among self-employed workers. Using unique data from 1602 Russian-language internet freelancers, who are typically both contract professionals and teleworkers, we investigate the relatedness of education and work in this new occupational and social context. We provide rare evidence of the effects of horizontal educational mismatch on earnings, job satisfaction, and perceived job mobility of self-employed workers. We find that educational mismatch has differential influence on women's and men's experiences. Although both men and women have an earnings penalty for being mismatched, only mismatched women suffer from reduction in job satisfaction. Women who work outside their field of study while caring for their small children are in the most vulnerable position. They experience negative socio-economic outcomes in all dimensions: reduction in earnings, job satisfaction, and express intentions to change their current employment situation. We argue that these findings may be evidence of gendered career strategies and greater family demands for women in the new economy.